(untitled) (Papeles, 2022)
The political constitution of Colombia from 1991 has been recognized as an ecological constitution because, in terms of environmental justice, it expanded the mechanisms for environmental protection, reflected in the rights and obligations of the State and individuals. However, environmental conflicts and crimes in the country continue increasing. Therefore, the question is: How can Colombia establish an environmental justice system? One of the strategies has been to adopt elements of ecological justice through numerous judicial pronouncements, they have recognized ecosystems as subjects of rights, leaving behind the understanding of Nature as an object. However, this recognition is confronted with an anthropocentric legal system that hinders the execution of judicial orders, generating a phenomenon of accumulation of jurisprudence with relevant legal contributions, but without effectiveness, and this prevents ecological justice from being established in Colombia. Despite these important advances, the protection of nature and the consolidation of ecological justice in the country still continue being a challenge, because the structures that justify the domination of Nature have to be questioned, making necessary to rethink the models of justice that contribute to its reparation and restoration. Therefore, from the perspective of ecological justice, an analysis of environmental crimes in Colombia is made also an approach to alternative legal institutions specialized in the rights of Nature, in order to elucidate the path for ecological justice in Colombia.